Self awareness of a leader in Islam: ideal and possibility - Abd Rashid, Adnan (Leena & Luna International, Oyama, Japan, 2015)
Goodness and morality are the basic pillars that maintain the structure of every healthy organisation. Having a good character ensures that a leader behaves properly towards other members of undertaken organisation and this will keep social order in management. Din-al-Islam, explicitly cultivates in every Muslim leader the awareness of accountability and responsibility before Allah which is very crucial for Islamic management. The sphere of awareness builds up sincerity in one’s life or a leader because one’s acts are actually free of external forces, and merely for Allah’s pleasure. He also nourishes a life of virtues such as piety, patience, always seeks repentance, truthfulness, fear, hope and love of Allah, reliance on Allah, thankful praise and so on. In fact, this sensitivity may avoid source of corruptions from all sort of management. If a leader is devoid or unaware of the sense of accountability and responsibility before Allah, he or she actually may get involved in sin and corruption. The beneficent tarbiyyah of a sense of accountability and responsibility may nourish a leader’s relationship of complete obedience and trust in Allah. More significantly, a leader who understands and realises his responsibilities and is mindful of these will act and behave in a good manner with a firm Iman and develop a strong relationship with Allah. This may enable a leader to carry out his acts and commitments in all spheres of management in an orderly way, to seek virtue by all possible means, to behave positively rather than destructively whether privately or publicly.